PANCASILA SEBAGAI LANDASAN PENDIDIKAN KARAKTER BANGSA - Sihotang, Samuel Efraim (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Character is one of the important aspects for a student. However, many students in Indonesia still do not have the character that a student should have. According to KPAI data, in 2018 there was an increase in brawl cases of 1.1% (KPAI, 2020). This shows that the character of students in Indonesia is still very deviant. Therefore, it is necessary to create awareness among students to have character. One way is to apply Pancasila as a basis for cultivating the character of the nation's student